2006
DOI: 10.1007/s00270-005-0379-3
|View full text |Cite
|
Sign up to set email alerts
|

A Survival Analysis of Patients with Malignant Biliary Strictures Treated by Percutaneous Metallic Stenting

Abstract: Percutaneous metallic biliary stenting provides good palliation of malignant jaundice. Partial liver drainage achieved results as good as those after complete liver drainage. A serum bilirubin level of less than 4 mg/dl after stenting is the most important independent predictor of survival, while increasing age and Bismuth IV lesions represent dismal prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
79
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 24 publications
14
79
2
Order By: Relevance
“…This retrospective study was designed to investigate the clinical efficiency, as judged by survival and relief from jaundice symptoms, following percutaneous bi-lobar stenting for the management of Bismuth Ⅳ malignant disease. Bismuth Ⅳ disease has been identified as an independent predictor of almost 5-fold increased mortality following PTBS [17] . In this series the mean survival time of 169 d is comparable and even superior to previously reported results involving patients with less advanced, Bismuth Ⅰ -Ⅳ, disease [2,3] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This retrospective study was designed to investigate the clinical efficiency, as judged by survival and relief from jaundice symptoms, following percutaneous bi-lobar stenting for the management of Bismuth Ⅳ malignant disease. Bismuth Ⅳ disease has been identified as an independent predictor of almost 5-fold increased mortality following PTBS [17] . In this series the mean survival time of 169 d is comparable and even superior to previously reported results involving patients with less advanced, Bismuth Ⅰ -Ⅳ, disease [2,3] .…”
Section: Discussionmentioning
confidence: 99%
“…In very advanced disease the clinical effectiveness of single-lobe drainage remains controversial as some authors have reported superior patency rates and clinical outcomes in patients with Bismuth type Ⅳ obstruction when both biliary ducts were stented [12] . Furthermore, in cases of extensive right lobe tumour, unilateral right bile drainage could result in insufficient serum bilirubin level decrease, a clinical endpoint that has been identified as a main independent predictor of survival [17] . On the other hand, single left lobe drainage is rarely sufficient to eliminate or ease obstructive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant obstructive jaundice can lead to hyperbilirubinemia, anorexia, pruritus, cholangitis, septicemia and liver failure. Generally, surgical resection remains the primary treatment for malignant obstructive jaundice; however, in numerous cases the malignant obstructive jaundice is detected when the disease is already at an advanced stage (2). For the patients that are unable to undergo surgery, urgent treatment is required to improve hepatic function, in order to facilitate the addition of subsequent anti-tumor therapy to their treatment regimen.…”
Section: Introductionmentioning
confidence: 99%
“…In the sixth month, the cumulative patency rate was 50%. Overall, mean primary patency rates in different series were between 141 and 231 days (8)(9)(10)(11)(12)(13)(14)(15). In the study by Maybody et al (10), an overall mean primary patency rate of 227.7 days was found in patients with multiple noncoaxial stents.…”
Section: Discussionmentioning
confidence: 94%